A survey of the mental healthcare systems in five Francophone countries in West Africa: Bénin, Burkina Faso, Côte d'Ivoire, Niger and Togo. Issue 3 (August 2014) - Maiga, Djibo Douma; Eaton, Julian
Abstract : Sub-Saharan Africa has a wide mental health treatment gap, with low levels of access to mental health services. This paper presents the findings of systematic situation analyses carried out in five Francophone countries in West Africa, which are among the poorest in the world. The findings showed low levels of budgetary allocation to mental health, poor health infrastructure (especially at primary level) and unequal distribution of human and financial resources. In this challenging context, there are signs of reform of services, based on international best-practice guidelines and practical considerations such as decentralisation of services, task-sharing and strengthening stakeholder skills to advocate for change.